Resolution of right atrial thrombus shown by serial cross sectional echocardiography. Issue 6 (June 1985) - Brown, A K; Anderson, V
Abstract : A 78 year old woman with congestive cardiac failure developed pulmonary embolism. Cross sectional echocardiography detected an undulating fusiform mass attached to the lateral wall of the right atrium and protruding through the tricuspid valve. Serial cross sectional echocardiograms showed a reduction in the size of the mass, and by three months the mass was immobile and attached by a broad base to the lateral atrial wall. The mass was assumed to be a thrombus, and treatment with heparin and oral anticoagulants appeared to prevent the development of further pulmonary emboli.